Analisi Implementasi Contractor Safety Management System (CSMS) Pada Tahap Pelaksanaan Pekerjaan Proyek Kapal Tanker Di PT. Daya Radar Utama Unit Lampung Tahun 2019 - ratna muliawati; Nur Sefa Arief Hermawan (JIKMI (Jurnal Ilmu Kesehatan Masyarakat Indonesia), 2020)
AbstractThe contractor plays an important role in supporting the operations of a company. However, contractors are more prone to work accidents because they directly carry out work activities. Contractor Safety Management System (CSMS) is a management system for managing contractors who work within the PT. Pertamina. The purpose of this study was to analyze the implementation of a Contractor Safety Management System (CSMS) at the stage of implementing the Tanker project at PT. Main Radar Power Unit of Lampung in 2019. This study uses a qualitative approach by triangulation to understand a phenomenon of CSMS implementation. The informants of this study consisted of 1 person from HSE PT. Pertamina and each 1 General Manager of Production, 1 person HSE Coordinator, 1 person Project Manager, 2 Workers PT Lampung Unit DRU. The results showed that the implementation of CSMS in the Pre-Work Phase which was divided into 6, namely PreJob Meeting, HSE Plan and HSE Induction. Then the Ongoing Work phase which is divided into 5 activities, namely Daily Inspection, HSE Management Visit, Audit, Safety Meeting Contractor and Tool Box Meeting have not been carried out maximally by PT. Lampung Unit DRU. It is recommended to PT. Daya Radar Utama to support both financially, human resources and communication in the HSE field for the implementation of CSMS at the work implementation stage so that PT DRU Unit Lampung is able to realize all HSE programs properly.Keywords : Contractor Safety Management System (CSMS), Contractor.